Consequence of an unbalanced supplyng condition on a distribution transformer - Vernieri, Julieta Zulema (2001)
Most of the time transformers work under balanced supplying conditions. However, after some fault conditions or anomalous switching operations, zero sequence component in excitation may be expectable. Transformers behavior under zero sequence excitation may be very different from usual behavior and might become dangerous. Some simulations are performed with the Alternative Transients Program (ATP), representing a three-legged core type three-phase transformer with a model available in the ATP library.